Cover Image, Volume 29, Issue 4. (April 2016) - Marty, Benjamin; Baudin, Pierre‐Yves; Reyngoudt, Harmen; Azzabou, Noura; Araujo, Ericky C. A.; Carlier, Pierre G.; de Sousa, Paulo L.
Abstract : The cover image, by Benjamin Marty, is based on the Research Article Simultaneous muscle water T2 and fat fraction mapping using transverse relaxometry with stimulated echo compensation, DOI:10.1002/nbm.3459 .